2018
DOI: 10.1155/2018/4984659
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Immunomodulator Activities of Allium sativum L.

Abstract: Allium Sativum L. (garlic), which is a species of the onion family, Alliaceae, is one of the most used plants in traditional medicine worldwide. More than 200 chemicals with diverse properties have been found in garlic extracts. Several garlic compounds were suggested to be efficient in improving various pathologies including certain types of cancer. This paper is an overview of data about garlic biological activities in vitro and/or in vivo on immune cells, on the development of certain inflammatory diseases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 98 publications
0
45
0
3
Order By: Relevance
“…De manera similar, son también recursos potenciales y efectivos en la prevención y/o tratamiento del COVID-19, Zingiber officinale " kion'', muy empleado alrededor del mundo como condimento de sopas y numerosos "platillos", y el que ampliamente estudiado ha demostrado tener gingeroles, shogaoles y paradoles, de acción antiviral, de virus respiratorios, además de su efectiva acción antiinflamatoria para la artritis, reumatismo y menopausia (Gil, 2020;Grzanna et al, 2005). De igual manera, destaca Allium sativum "ajo'', con numerosas propiedades antivirales, antioxidantes, antiinflamatorias, antitumorales, antihipertensivo, antiagregante plaquetar, entre otros; y que también su acción antiviral ha sido demostrada contra la bronquitis aviar (IBV) por coronavirus, virus influenza A y B, parainfluenza tipo 3, citomegalovirus, rinovirus, virus herpes y rotavirus (Bayan et al, 2014;El-Saber et al, 2020;Gil, 2020;Mohajer et al, 2016); efecto debido a la presencia de S-alil-cisteína (aliina) y alil-2propeniltiosulfinato (alicina), que mantienen la homeostasis del sistema inmune, estimulando a los linfocitos y macrófagos citotóxicos; además de reducir la presión arterial hasta en un 7% u 8% de las personas hipertensas, pudiendo también disminuir la coagulación, favoreciendo igualmente la disolución de trombosis ocasionado por coronavirus (Gómez, 2019;Moutia et al, 2018). Por otra parte, Eucalyptus globulus " eucalipto '', recurso medicinal muy empleado para tratar afecciones respiratorias como resfriados, dolor de garganta, faringitis, gripe, bronquitis, sinusitis, asma, neumonía, también posee acción antiviral, antiséptica y expectorante; por contener cineol, α y β-pineno, y limoneno (Carretero y Ortega, 2018).…”
Section: Resultados Y Discusiónunclassified
“…De manera similar, son también recursos potenciales y efectivos en la prevención y/o tratamiento del COVID-19, Zingiber officinale " kion'', muy empleado alrededor del mundo como condimento de sopas y numerosos "platillos", y el que ampliamente estudiado ha demostrado tener gingeroles, shogaoles y paradoles, de acción antiviral, de virus respiratorios, además de su efectiva acción antiinflamatoria para la artritis, reumatismo y menopausia (Gil, 2020;Grzanna et al, 2005). De igual manera, destaca Allium sativum "ajo'', con numerosas propiedades antivirales, antioxidantes, antiinflamatorias, antitumorales, antihipertensivo, antiagregante plaquetar, entre otros; y que también su acción antiviral ha sido demostrada contra la bronquitis aviar (IBV) por coronavirus, virus influenza A y B, parainfluenza tipo 3, citomegalovirus, rinovirus, virus herpes y rotavirus (Bayan et al, 2014;El-Saber et al, 2020;Gil, 2020;Mohajer et al, 2016); efecto debido a la presencia de S-alil-cisteína (aliina) y alil-2propeniltiosulfinato (alicina), que mantienen la homeostasis del sistema inmune, estimulando a los linfocitos y macrófagos citotóxicos; además de reducir la presión arterial hasta en un 7% u 8% de las personas hipertensas, pudiendo también disminuir la coagulación, favoreciendo igualmente la disolución de trombosis ocasionado por coronavirus (Gómez, 2019;Moutia et al, 2018). Por otra parte, Eucalyptus globulus " eucalipto '', recurso medicinal muy empleado para tratar afecciones respiratorias como resfriados, dolor de garganta, faringitis, gripe, bronquitis, sinusitis, asma, neumonía, también posee acción antiviral, antiséptica y expectorante; por contener cineol, α y β-pineno, y limoneno (Carretero y Ortega, 2018).…”
Section: Resultados Y Discusiónunclassified
“…Major organosulfur compounds found in garlic oil, such as diallyl disulfide and diallyl trisulfide, were proposed to suppress BC by halting DNA formation, inhibiting the production of reactive oxygen species, regulating cell cycle arrest, and inducing apoptosis . Garlic was also shown to play a critical role in maintaining homeostasis of the immune system . Hodge et al confirmed that fresh garlic extract played a role in suppressing Th1 and inflammatory cytokine production, as well as upregulating the production of IL‐10.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic has been used since ancient times to suppress the growth of bacteria, fungi and viruses (21). It has been demonstrated that garlic extract and its components attenuate atherosclerosis (22) and hypertension (23), and exert immunomodulatory and anti-tumor effects (24). It has also been found that the aqueous extract of garlic (21,25) and its components, allicin (26) and diallyl sulfide (27), inhibit the growth of the periodontal pathogens, P. gingivalis, Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum in vitro.…”
Section: Evidence Of the Inhibitory Effect Of Various Naturally Occurmentioning
confidence: 99%